Humanisasi Pendidikan Islam Melalui Konseling Qur’ani: Menjawab Tantangan Individualisme dan Materialisme Global - Reyhanna Fadillah; Kelvin Afriansyah Purba (Arba: Jurnal Studi Keislaman, 2025)
The development of the globalization era has had a significant impact on the mindset and behavior of the younger generation, particularly the emergence of challenges to individualism and materialism that erode the values of humanity and spirituality in Islamic education. This phenomenon demands an educational model that is able to integrate Qur’anic values ​​in building the character of students holistically. This study aims to examine the role of Qur’anic counseling as an effort to humanize Islamic education in facing the challenges of global individualism and materialism. The research method used is qualitative with a descriptive-analytical approach, examining the texts of the Qur’an and Islamic counseling literature to understand the concept and practice of Qur’anic counseling in the context of education. The results of the study indicate that Qur’anic counseling is capable of restoring the balance between spiritual and social values, instilling awareness of individual responsibility towards society, and reducing the influence of excessive materialistic values. This approach strengthens noble morals and empathy as the foundation of humanizing Islamic education that is relevant to the current global context. In conclusion, Qur’anic counseling is a strategic solution in revitalizing Islamic education to be more humane and oriented towards the formation of individuals with integrity and high civilization. Its practical implications can be applied in the curriculum and character building in Islamic educational institutions.